Multidisciplinary approach for reconstruction of cranial defect with polymethyl methacrylate resin reinforced with titanium mesh - Vikrant Dilip Sane; Pankaj Kadam; Aniket Jadhav; Rashmi Saddiwal; Yash Merchant (Wolters Kluwer Medknow Publications, 2016)
Cranial defects occur most commonly as a sequelae to trauma, the incidence being as high as 70%. The successful management of a case of trauma in an emergency situation requires quick evacuation of the hematoma, repair of the dura, and the scalp but not necessarily the integrity of the calvarial segment as an immediate measure. So the reconstruction of the calvarial defect in these cases is mostly carried out as a secondary procedure. Various materials are used for reconstruction of cranial defects, polymethyl methacrylate (PMMA) resin being one of them. In this article, we report a case which was successfully treated by PMMA resin in combination with a titanium mesh for reconstruction of the cranial defect as a secondary procedure.